Hepatic and Renal Histopathological Effects of Local Fruit Juices containing Sodium Benzoate as Preservative: Histopathological effects of locally packed fruit juices on liver & kidney of mice - Mehdi, Muhammad Muntazir; Javed, Anam; Hoti, Afraseyab Khan; Naheed, Sabahat (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Packed fruit juices are commonly consumed on daily basis around the globe which usually contains sodium benzoate as food preservative to enhance their shelf life and its amount may vary from defined food standards among brands. This mammalian model based research was designed to investigate the impact of locally packed fruit juices’ regular intake on consumers. For this purpose, albino mice (Mus musculus) were acclimatized in laboratory environment for ten days and then categorized in control and two experimental groups. The selected local brands were Murree brewery lemon malt and Shezan mango juice and their 0.1ml prepared dose was given to experimental groups I and II, respectively, whereas; control group was treated with equivalent amount of distilled water. The obtained histopathological results emphasized that regular intake of sodium benzoate having fruit juices may cause severe damage to hepatic and renal tissues, usually in the form of necrosis, vascular congestion sometimes dilation and other cellular alterations i.e., in glomeruli and bile duct. Moreover, it may result in onset of tumorogenesis. The conclusion of this study is local food authorities should ensure the addition of a defined amount of sodium benzoate as juice preservative in locally packed juices to provide healthy products to consumers.